Analisis Pengaruh Dukungan Keluarga, dan Faktor Lainnya terhadap Pemberian Imunisasi MR pada Balita - Saka Adhijaya Pendit; Tria Astika; Nana Supriyatna (Jurnal Keperawatan Silampari, 2019)
This study aims to determine the relationship of family support and other factors in participating in MR immunization in Posyandu in the work area of Momunu Health Center, Buol Regency, Central Sulawesi. This study uses a cross sectional design. The number of research respondents was 96 respondents. The results of this study indicate that (p value 0.005) for the variable family support for MR immunization, for the nurse support variable for MR immunization (p-value 0.007) and for the education variable for MR immunization (p-value 0.012). Conclusion, there is a significant relationship between family support for [giving immunization, there is a relationship between nurse support for giving immunization and there is an educational relationship with giving immunization. Keywords: Measles and Rubella, Family Support, Giving Immunization MR